Exploring the effect of eye gaze cues on novel L2 morphosyntactic pattern learning. (January 2022) - Abashidze, Dato; McDonough, Kim; Gao, Yang
Recent research that explored how input exposure and learner characteristics influence novel L2 morphosyntactic pattern learning has exposed participants to either text or static images rather than dynamic visual events. Furthermore, it is not known whether incorporating eye gaze cues into dynamic visual events enhances dual pattern learning. Therefore, this exploratory eye-tracking study examined whether eye gaze cues during dynamic visual events facilitate novel L2 pattern learning. University students ( n = 72) were exposed to 36 training videos with two dual novel morphosyntactic patterns in pseudo-Georgian: completed events ( bich-ma kocn-ul gogoit, 'boy kissed girl') and ongoing actions ( bich-su kocn-ar gogoit, 'boy is kissing girl'). They then carried out an immediate test with 24 items using the same vocabulary words, followed by a generalization test with 24 items created from new vocabulary words. Results indicated that learners who received the eye gaze cues scored significantly higher on the immediate test and relied on the verb cues more than on the noun cues. A post-hoc analysis of eye-movement data indicated that the gaze cues elicited longer looks to the correct images. Findings are discussed in relation to visual cues and novel morphosyntactic pattern learning.